Pedro Pascal - Connors, Kathleen (Icons, 2026)
"It seems like Pedro Pascal is popping up in everything these days! He's been in some of the biggest TV shows of the past decade, including Game of Thrones and The Mandalorian. He's been named one of Time magazine's most influential people and even appeared on Broadway! This book introduces readers to Pedro's early life and his path to stardom, starting with his birth in Chile and childhood in Texas. Full-color photographs complement the low-level text and help highlight Pedro's career through the years"--